OPTIMASI PENGIRIMAN BAHAN BAKU PADA PERUSAHAAN LAPTOP MENGGUNAKAN METODE NORTH WEST CORNER - Fadzell Auraffa Ahmad; Fakhri Nur Faishal, Fathan Abdullah Putranto, Paduloh (ADISAM PUBLISHER, 2025)
Technological developments and intense competition in the service and manufacturing sectors require efficient management, especially in dealing with rising shipping costs due to exchange rate fluctuations. Goods distribution problems, which involve constraints such as variations in demand and vehicle capacity, require the implementation of transportation methods to minimize costs. This study examines the use of the North West Corner (NWC) method and the Stepping Stone technique in laptop delivery, aiming to allocate resources effectively and reduce transportation costs, thereby increasing distribution efficiency and company profitability